Paul: ΣОФОΣ and ПNΕΥΜΑΤΙΚΟΣ - Scroggs, Robin (New Testament studies, 1967)
The first two chapters of I Corinthians are an important source for illuminating Paul's understanding of his missionary proclamation and teaching. The evidence is, however, by no means unambiguous and has been variously assessed. At one extreme stands a view such as that of Hans Windisch, who believes that Paul's christology here, as elsewhere, has been decisively influenced by Jewish wisdom teaching. Completely in the opposite direction goes the recent work of Ulrich Wilckens, who rejects any essential relationship between Paul and wisdom theology. Wilckens's studies represent a prominent tendency in recent scholarship and well merit more detailed exploration than the outline that is possible here. According to this scholar the Corinthian opponents are gnostics. Their wisdom is derived not from Greek rhetoric but from a revelatory theology whose chief offence to Paul is that it denies significance to the cross. Yet in the crucial section, I Cor. ii. 6–16, Paul himself would almost appear to be the gnostic, so similar are his words and ideas to gnostic views. The apostle's language here stems, however, from the Corinthian theology, not from his own characteristic thought. What Paul intends to do is in fact to attack the gnostic christology; but since he actually shares many ideas with the gnostics, this section, despite its intent, could actually be taken entirely in the gnostic sense. The paradoxical result of Wilckens's argument is that in those sections where Paul describes the Corinthian wisdom, one finds only Paul's derogatory and inaccurate judgement, while in the section where Paul would seem to be speaking of his own wisdom teaching, one can see the real view of the Corinthians.